Spiritualitas Alam dalam Kumpulan Cerita Pendek Digital Lakon Hidup.com (Perspektif Ekofeminisme) - A. Shabirah Alfiyyah W.; Hajrah Hajrah; Faisal Faisal (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract.This study aims to describe the representation of immanence, interconnectedness, and caring lifestyle of Starhawk contained in the collection of short stories Lakon Hidup which is used as the source of the analyzed data. This study uses a descriptive qualitative method by describing the data obtained based on the theory of Spiritual Ecofeminism Starhawk. The data source of this research is a collection of shorts stories on the life play page published by Kompas in 2017-2021 as many as 5 short stories. The result of this study is to indicate the woman’s representation in short stories as a symbol of fertility and mother role in nature preservation. Keywords: Ecofeminism, Nature Spirituality, Starhawk Spritual Ecofeminism.